Parental perceptions of e-cigarette and vaping usage among single-sex, school-going adolescents in Toronto, Canada - Crossland, J. (The Young Researcher)
This study explores parental perceptions of adolescent e-cigarette usage, specifically, examining adolescents who attend independent private schools in Toronto, Canada, in order to investigate if those of high socioeconomic status are more educated on the issue of increasing adolescent nicotine consumption. This study employs a quantitative, non-experimental research methodology through the use of surveys administered to parents who have a child at one of the two used independent private schools. This study finds that parents are largely unaware of the increasing e-cigarette usage within schools and more generally, across the globe. Additionally, it finds that parents are unaware of the health risks associated with e-cigarette usage. This study also finds a strong relationship between parental substance use and adolescents perceived risk of substance use. Mainly, it shows that if an adolescent has a parent who smokes or uses substances, that adolescent will have a positive view on substance use, resulting in a greater likelihood of usage in the future. These findings imply that governments and schools have not been effective in preventing this health epidemic and have not been educating parents and adolescents on the potential risks of e-cigarette usage and nicotine consumption.